Postpartum Outcomes in Women with Gestational Diabetes and their Offspring: POGO Study Design and First-Year Results - Hummel, Sandra (SBDR - Society for Biomedical Diabetes Research, 2013)
BACKGROUND: Gestational diabetes mellitus (GDM) is a risk factor for mothers to develop type 2 diabetes (T2D) postpartum, and for their children to develop obesity. The aim of the ongoing POGO study is to identify long-lasting changes in the maternal and fetal metabolism and microbiome, after GDM, which contribute to subsequent development of T2D and obesity. METHODS: Women screened for GDM are asked to attend a postpartum study visit together with their offspring. At the visit, demographic, nutritional, and anthropometric data are recorded. Additionally, data about physical activity, metabolism, and genetic susceptibility are collected using accelerometers, breath gas analyses, 75g oral glucose tolerance tests (OGTT), and bio-samples such as blood and stool. RESULTS: To date, 121 women (median follow-up time postpartum: 5.5 years) have been enrolled together with 133 index children. GDM has been diagnosed using OGTT in 105 women (and 117 children). It showed that 47 mothers had abnormal glucose tolerance, including 19 cases of impaired glucose tolerance, 19 of impaired fasting glucose, eight with T2D, and one with type 1 diabetes (T1D). The prevalence of obesity in the offspring of GDM mothers was 5.1%. Of 61 children tested by OGTT, three were diagnosed with impaired glucose tolerance, another three with impaired fasting glucose, and none with T1D or T2D. CONCLUSIONS: The POGO study will contribute to the understanding of the pathogenesis of T2D and obesity after GDM, and will thus help to develop appropriate prevention and intervention strategies. This article presents the first results of the ongoing study, which are looking promising.